Where Asia meets Europe – recent insights from ancient human genomics. (3rd April 2021) - Feldman, Michal; Gnecchi-Ruscone, Guido A.; Lamnidis, Thiseas C.; Posth, Cosimo
Abstract: Context: The peopling of Europe by modern humans is a widely debated topic in the field of modern and ancient genomics. While several recent syntheses have focussed on this topic, little has been discussed about the genetic history of populations in the continent's surrounding regions. Objective: We explore genetic transformations in three key areas that played an essential role in the formation of the European genetic landscape through time, focussing on the periods spanning from the Epipalaeolithic/Mesolithic and up until the Iron Age. Methods: We review published ancient genomic studies and integrate the associated data to provide a quantification and visualisation of major trends in the population histories of the Near East, the western Eurasian Steppe and North East Europe. Results: We describe cross-regional as well as localised prehistoric demographic shifts and discuss potential research directions while highlighting geo-temporal gaps in the data. Conclusion: In recent years, archaeogenetic studies have contributed to the understanding of human genetic diversity through time in regions located at the doorstep of Europe. Further studies focussing on these areas will allow for a better characterisation of genetic shifts and regionally-specific patterns of admixture across western Eurasia.